2010
DOI: 10.1128/jvi.00678-10
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Papillomavirus E8∧E2C Protein with the Cellular CHD6 Protein Contributes to Transcriptional Repression

Abstract: Expression of the E6 and E7 oncogenes of high-risk human papillomaviruses (HPV) is controlled by cellular transcription factors and by viral E2 and E8 ∧ E2C proteins, which are both derived from the HPV E2 gene. Both proteins bind to and repress the HPV E6/E7 promoter. Promoter inhibition has been suggested to be due to binding site competition with cellular transcription factors and to interactions of different cellular transcription modulators with the different amino termini of E2 and E8 ∧ E2C. We have now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 84 publications
(121 reference statements)
1
17
0
1
Order By: Relevance
“…S1 in the supplemental material), which has been demonstrated by single-amino-acid mutations (W6A and K7A) to be sufficient for repressing the replication of HPV31 genomes (39,46). This also suggests that the repression activities of all ␣-HPV E8^E2C proteins might be due to a conserved interaction of the E8 domain with an HDAC3/NCoR complex, as demonstrated for 31E8^E2C, and also to interaction with the CHD6 protein via the E2C domain (11,31).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…S1 in the supplemental material), which has been demonstrated by single-amino-acid mutations (W6A and K7A) to be sufficient for repressing the replication of HPV31 genomes (39,46). This also suggests that the repression activities of all ␣-HPV E8^E2C proteins might be due to a conserved interaction of the E8 domain with an HDAC3/NCoR complex, as demonstrated for 31E8^E2C, and also to interaction with the CHD6 protein via the E2C domain (11,31).…”
Section: Discussionmentioning
confidence: 73%
“…Recent studies have indicated that transcriptional repression of the HPV URR by the E2 and 31E8^E2C proteins is due to interaction with different sets of cellular proteins via the amino termini and to a conserved interaction of the E2C domain with CHD6 (11). The transcriptional-repression activity of E2 has been linked to the interaction with the cellular Brd4, SMCX, and EP400 proteins (35,45).…”
Section: Discussionmentioning
confidence: 99%
“…The HPV31 E8/E2 protein represses transcription and extra-chromosomal replication; many interactions responsible for these repressive functions are described. [41][42][43] However, the HPV31 E8 and BPV1 E8 proteins belong to different E8 clades (Puustusmaa and Abroi, manuscript in preparation). In addition, the subcellular localization of HPV31 E8/E2 has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca, HPV-1 ve HPV-31'de viral transkripsiyon ve replikasyonun bir negatif düzenleyici olarak E8-E2 füzyon proteini belirlenmiştir 8,9 . E8 geninin bir parçası olan E8-E2 füzyon proteini, E2 geninin C terminaline bağlanmış olup, viral transkripsiyonun alternatif bir yolunu oluştur-maktadır 16 . E8-E2C'nin viral yaşam siklusunun erken evresi boyunca HPV DNA replikasyonunun negatif bir düzenleyicisi olduğunu düşünülmektedir 17,18 .…”
Section: Hpv Genomu Proteinleri Ve Replikasyonuunclassified